CRITICAL REVIEW ON HOMELESS, VAGRANTS AND DESTITUTE ACTS IN MALAYSIA AND SELECTED COUNTRIES: HEALTHCARE PERSPECTIVE - Roslina Mohamad Shafi; Sharazad Haris; Mohd Hakimi Harman; Faridah Najuna Misman; Mohamed Eskandar Shah Mohd Rasid (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Issues of homelessness have existed for many years, and to date, the number of homeless is on the rise, and most went unrecorded. Recent global pandemics, changes in social needs, and economic pressure, among others, have contributed to this statistic. A high number of homeless in a country is a sign that guaranteed access to safe, affordable, and adequate housing for the citizens is not yet met. Society’s stigma that equates homeless to crime and violence further aggravated the problem, withholding their right to attain appropriate standards of living and the highest standard of healthcare. Even though legislation on homelessness and vagrancy exists, most are dated, hindering the effort to cater to this issue. Accordingly, this study aims to provide an overview of current legislation and to identify any drawbacks in the said legislation, especially from the healthcare perspective. The study applied a narrative review method. The review question is specific to the content related to the definition of homeless and clauses related to healthcare, focusing on countries such as Malaysia, Australia, Unites States of America, Canada, Finland, Qatar and the United Kingdom. The study concludes with a summary of the research findings, identifying gaps in the legislation and providing insights into recommendations for developing and implementing policies to promote healthcare affordability among the homeless.